Clinical trials on carotenoids and vitamin mineral supplements in ophthalmology - A.A. Gvetadze; M.G. Rabadanova (РМЖ "Клиническая офтальмология")
A.A. Gvetadze1, M.G. Rabadanova1,2 1City Clinical Hospital №15, Moscow, Russian Federation 2Pirogov Russian National Research Medical University, Moscow, Russian Federation This article reviews some of the large-scale multicentral clinical trials on lutein, zeaxanthin, and vitamins and minerals (AREDS 1, 2001; AREDS 2, 2006; LUNA, 2006; CARMA, 2006). The authors discuss etiology and pathogenesis of age-related macular degeneration (AMD) as well as the role of oxidative stress. Retinal protective effect of lutein and zeaxanthin is highlighted. Key markers of the efficacy of the preventive treatment with carotenoids were identified, i.e., increased macular pigment optical density, the presence of lutein and zeaxanthin in blood serum, and improved vision (visual acuity, contrast sensitivity etc.). Potential risks of the progression of early AMD to the advanced disease were calculated. Recent published data from these trials have systematized current information and enabled to perform meta-analysis of trials on vitamin mineral supplements. Key words: carotenoids, nutrients, oxidative stress, vitamin mineral supplements, lutein, zeaxanthin, antioxidant, retinal protection, macular pigment optical density, age-related macular degeneration, clinical trials, meta-analysis. For citation: Gvetadze A.A., Rabadanova M.G. Clinical trials on carotenoids and vitamin mineral supplements in ophthalmology. Russian Journal of Clinical Ophthalmology. 2019;19(1):38–41. About the authors: 1Anna A. Gvetadze — MD, PhD, ophthalmologist; 1,2Madina G. Rabadanova — MD, PhD, Associate Professor of Ophthalmology Department, ophthalmologist. 1 City Clinical Hospital №15. 23, Veshnyakovskaya str., Moscow, 111539, Russian Federation. 2Pirogov Russian National Research Medical University. 1, Ostrovityanova str., Moscow, 117997, Russian Federation. Contact information: Anna A. Gvetadze, e-mail: gvetadzanya@mail.ru. Financial Disclosure: no authors have a financial or property interest in any material or method mentioned. There is no conflict of interests. Received 09.11.2018.